Compromiso gástrico exclusivo en enfermedad de Crohn. - Braghetto, Italo; Smok, Gladys; Olavarría, Gino; Debandi, Anibal; Korn, Owen (Revista Hospital Clínico Universidad de Chile, 1998)
Resumen no disponible.